2015
DOI: 10.1002/anie.201506435
|View full text |Cite
|
Sign up to set email alerts
|

Autoresolution of Segregated and Mixed p‐n Stacks by Stereoselective Supramolecular Polymerization in Solution

Abstract: A "chirality driven self-sorting" strategy is introduced for the controlled supramolecular organization of donor (D) and acceptor (A) molecules in multicomponent assemblies. The trans-1,2-bis(amido)cyclohexane (trans-BAC) has been identified as a supramolecular motif with strong homochiral recognition to direct this chirality controlled assembly process of enantiomers in solution. Stereoselective supramolecular polymerization of trans-BAC appended naphthalene diimide monomers (NDIs) has been probed in detail b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…[8b] Thea bsorption spectrum of 1 shows two distinct absorption bands.The absorption band below 400 nm corresponds to the electronic transition along the long axis of the NDI core. [21][22][23][24][25] These results indicate that the electronic coupling between the NDI p-orbitals in the selfassembled system is limited owing to the interruption of the strong p-p stacking interactions between NDI cores by the ethoxy groups. [27] Thes tructure of the latter band is almost retained even after self-assembly whereas broadening was observed for the former band.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8b] Thea bsorption spectrum of 1 shows two distinct absorption bands.The absorption band below 400 nm corresponds to the electronic transition along the long axis of the NDI core. [21][22][23][24][25] These results indicate that the electronic coupling between the NDI p-orbitals in the selfassembled system is limited owing to the interruption of the strong p-p stacking interactions between NDI cores by the ethoxy groups. [27] Thes tructure of the latter band is almost retained even after self-assembly whereas broadening was observed for the former band.…”
mentioning
confidence: 99%
“…Theb uilding blocks of supramolecular assemblies play adecisive role in dictating their functional properties.The use of PDIs [7a] in this regard has been well established in the literature;more recently,ithasbeen reported that NDIs also fall into this category. [20][21][22][23][24][25][26] Fore xample,G eorge and coworkers reported that a trans-1,2-diamide cyclohexane derivative bearing two NDI units (2;S cheme 1) underwent autoresolution during enantioselective self-assembly,demonstrating its chiral recognition capability. [25b] However, 2 is less emissive,w hich limits studies based on energy transfer and CPL.…”
mentioning
confidence: 99%
“…339 George and coworkers reported the co-assembly of pconjugated amphiphilic building blocks. [340][341][342][343][344][345][346] Using the electron-rich coronene/electron-deficient methyl viologen pair, 340 or oligo(phenylenevinylene) (OPV1)/perylene diimide (PDI1) pair, 341 the formation of supramolecular alternating electron-donor/acceptor arrays were obtained. Both comonomer pairs, the cationic viologen and the anionic coronene tetracarboxylate, and the cationic ammoniumfunctionalized PDI1 and the anionic OPV dicarboxylate OPV1 form charge transfer complexes and coassemble into 1-D nanofibers in water with an alternating comonomer arrangement, which from hydrogels at millimolar concentrations of the building blocks (Fig.…”
mentioning
confidence: 99%
“…In the recent past, examples showed that chirality might also lead to the self‐sorted assembly. George and co‐workers studied chirality driven self‐sorting of donor‐acceptor chromophores (Figure ) using trans‐1,2‐bis(amido) cyclohexane (BAC) supramolecular motif . They designed RR ‐NDI, SS ‐NDI, RR ‐DAN and SS ‐DAN building blocks (29–32) by linking the DAN/ NDI chromophores to the trans‐BAC motif.…”
Section: Discussionmentioning
confidence: 99%